Preparation and reconstruction of arbitrary path and polarization states in photons (2018)
The purpose of this monograph is to show how different discrete variables of light can be used to generate qubits. In particular, the tomographic preparation and reconstruction process for the polarization and path variables in photons is shown. In addition, the preparation of two-qubit states in a single photon using these variables is done, and these states are used to generate statistical mixtures states on the path. Finally, an experimental setup is proposed for the reconstruction of two-qubit states in a single photon. During the monograph, two different tomography techniques are used: Standard quantum state tomography and quantum state tomography through the use of mutually unbiased bases